Case Study on the Eligibility of Colombian Hass Avocado in the US Market: Opportunities in East Asia (2019)
The present case study succinctly presents events, circumstances and actors that participated in the official entry of the Colombian Hass avocado into the US market. The case exposes the characteristics of the global Hass avocado market and the challenges Colombia faces in complying with North American regulations regarding the admissibility and importation of fruits into its territory, in addition to its opportunities in the markets of East Asia. All the sources examined, and the academic analysis jointly carried out in the areas of international business and foreign trade, contributed to the construction of the case. The structure of the article responds to the writing characteristics of case studies for class analysis.